THE PATTERN OF DEVELOPMENT OF ISLAMIC EDUCATION (HISTORICAL STUDIES) - Tolchah, Moch (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
AbstractThis reseach aimed to determine the pattern of development of islamiceducation. The method used in this reseach was qualitative. The results ofthis research, the period before Indonesiaâs independence there are differentpatterns of development of Islamic education, namely: (1) isolatif-traditional,in the sense of not willing to accept anything that smells Western (colonial)and the inhibition effect of modern thinking in Islam to enter into it, as wasevident at the boarding school education featuring only traditional religioussciences of Islam and common knowledge is not at all given. The essenceof Islamic education is an effort to conserve and maintain the treasures ofearlier scholars thought as expressed in their books. The main purpose ofeducation is to prepare prospective chaplain or clergy only controlled religiousissues alone. (2)Synthesis, which brings the livery (Islamic boarding school)and the new style (colonial or Western education model) tangible schools orMadrasah. In reality, patterns of thought this synthesis contain some variationof the pattern of development of Islamic education. (3) Various models andpatterns of development of Islamic education are essentially intends to developteachings and fundamental values contained in the Quran and al-Sunnah.Itâs just that they have a different perspective to understand and describethe nature of Islamic education and science. This implies also to formulaseducational objectives, content / Islamic education materials as well as aspectsof the methodology.Â Keywords: Islamic Education, Madrasah, Boarding School, Modern School